A Dual-Channel 15 Gb/s PRBS Generator for a D-Band PMCW Radar Transmitter in 22 nm FDSOI - Probst, Florian; Engelmann, Andre; Koch, Manuel; Weigel, Robert (IEEE Wireless and Microwave Technology Conference, WAMICON 2023, 2023)
This work proposes an integrated baseband signal generator with multiple orthogonal outputs for phase-modulated continuous-wave (PMCW) radar. The circuit combines a linear-feedback shift register (LFSR), producing an m-sequence at a chip rate of 15 Gb/s, with a digitally implemented outer code (OC) generator. Different channels can be distinguished at the receiver through a slow-time modulation of the pseudo-random binary sequence (PRBS) with different Hadamard codes. The generator is integrated into a 1700×1300 μm² double-channel D-band radar transmitter on a 22nm fully-depleted silicon on insulator (FDSOI) technology, of which only 73×80 μm² are devoted to the baseband generator. A measurement setup is presented, where the transmitter’s D-band output signal is externally down-converted and sampled using a high-speed oscilloscope. In a series of offline digital signal processing (DSP) steps including correlation, accumulation and another correlation, the functionality of the proposed generator is demonstrated.<br
Keywords: Fully-depleted silicon on insulator (FDSOI); MIMO radar; phase-modulated continuous-wave (PMCW); joint radar-communication (RadCom); true single-phase-clock (TSPC)